Intravital & laser speckle investigations of the role of interleukin36 in myocardial ischaemia reperfusion injury; a new therapeutic target for the aged heart. (10th June 2022) - El-Awaisi, J; Kavanagh, D; Rink, M; Weston, C; Drury, N; Kalia, N
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): British Heart Foundation Introduction: Whilst blood flow restoration is critical following myocardial infarction (MI), ischemia-reperfusion injury (IRI) accounts for ~50% of the final infarct size. Elderly patients have a poorer prognosis which may be linked to increased coronary microvessels susceptibility to injury. The newly discovered and inflammatory cytokine, interleukin-36 (IL-36), could potentially mediate these disturbances. However, its role in myocardial IRI is not known. Aim: This study firstly aimed to determine whether IL-36 and its receptor (IL-36R) were present in the heart, whether their expression varied in an injury and age-related manner, and whether topical application of its cytokines on the beating heart induces an inflammatory response. Secondly, we determined whether coronary microcirculatory disturbances, overall blood ventricular perfusion, and infarct size post-IRI were modified by age. Lastly, we investigated whether an IL-36 receptor antagonist (IL-36Ra) could confer vasculoprotection and reduce myocardial infarction. Methods: Myocardial IRI was induced in adult (3-months) and aged (>18-months) mice. In some studies, recombinant mouse IL-36Ra (15ug/mouse) was injected intra-arterially. IL-36R/α/β, and VCAM-1 expression were investigated immunohistochemically or using western blots. Beating heart coronary microcirculation was imaged intravitally in vivo and also ex vivo using multiphoton microscopy. Topical cytokine application was also observed intravitally. Laser speckle contrast imaging was used to determine perfusion, and infarct size was measured using dual TTC/Evans Blue staining. Results: IL-36R/α/β were expressed predominantly on the microvasculature of murine hearts, with some cardiomyocyte expression also observed. Expression of IL-36R/α/β and VCAM-1 significantly increased with injury and age (see Table). Topical application of all IL-36 cytokines induced a significant (p<0.0001) inflammatory response in vivo. Significantly increased basal (p<0.0001) and IRI-induced (p<0.0001) neutrophil recruitment, and greater decreases in functional capillary density, was observed in aged mice compared to adults.  Neutrophils primarily adhered within coronary capillaries although in aged hearts remarkable venular adhesion was also identified. These events were mirrored in deeper myocardial layers when imaged using multiphoton microscopy. IL-36Ra significantly reduced inflammation (p<0.0001), infarct size (p<0.0001) and improved blood perfusion (p<0.0001) in both adult and aged mice. Conclusion: These novel results are the first to demonstrate myocardial presence of IL-36 and its receptor. Our novel findings of enhanced coronary microcirculatory perturbations associated with age may explain the poorer outcomes in elderly MI patients. Importantly, we are the first to demonstrate that targeting IL-36 was vasculoprotective and may be a potential novel therapy for treatment of myocardial IRI.